HUMAN RESOURCE MANAGEMENT STRATEGIES IN SUPPORTING INCLUSIVE EDUCATION: A CASE STUDY AT INCLUSIVE SCHOOL OF SENTRA SALSABILA PURWAKARTA - Mukti, Saepul; Fatimah, Nur; Sapitri, Wina; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the human resource management (HRM) strategies implemented to support inclusive education at the Inclusive School of Sentra Salsabila Purwakarta. Inclusive education is an approach that emphasizes equal access and learning opportunities for all students, including children with special needs. This research adopts a qualitative case study method, with data collected through in-depth interviews, direct observations, and document analysis. The findings reveal that the Inclusive School of Sentra Salsabila employs several integrated HRM strategies, such as recruiting teachers with expertise in inclusive education, providing regular training to enhance pedagogical competencies, and forming a support team involving educators, parents, and special education consultants. Additionally, the school has established periodic evaluation mechanisms to improve the quality of its educational services. The novelty of this research lies in its collaborative approach to HRM, emphasizing synergy among all stakeholders as the main pillar of inclusivity. These findings offer practical insights for other educational institutions seeking to develop inclusive programs. The study recommends further exploration of the long-term effectiveness of these strategies and their application in diverse educational contexts to strengthen the implementation of inclusive education in Indonesia.